Storage stability of refrigerated vacuum-packed and heat-sealed baye-baye - Sasana, Mark Jan Cadiz
The storage stability of refrigerated vacuum-packed (T1) and heat-sealed (T2) baye-baye was investigated by monitoring the changes in their physico-chemical and microbiological properties and their sensory attributes during storage.